ROLE OF ULTRASOUND IN DIAGNOSING ACUTE APPENDICITIS IN PEDIATRIC PATIENTS - Dr. Hemat Jangid (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Acute appendicitis is the most common surgical emergency in pediatric patients, yet diagnosis remains challenging due to atypical presentations and communication difficulties. Ultrasound offers a radiation-free alternative to computed tomography for appendicitis evaluation, with growing evidence supporting its diagnostic utility in pediatric populations. Methods: A prospective diagnostic accuracy study was conducted at Mahaveer Institute of Medical Science and Research from January to June 2022. Consecutive pediatric patients aged 5-16 years presenting with suspected acute appendicitis underwent standardized ultrasound examination using graded compression technique. Ultrasound findings were compared with histopathological examination as the gold standard. Diagnostic accuracy parameters including sensitivity, specificity, positive and negative predictive values were calculated, with subgroup analyses performed based on age, gender, body mass index, and symptom duration. Results: Among 320 enrolled patients, acute appendicitis was histopathologically confirmed in 187 cases (58.4%). Ultrasound demonstrated excellent diagnostic performance with sensitivity of 93.6% (95% CI: 89.2-96.7%), specificity of 90.9% (95% CI: 84.9-95.2%), positive predictive value of 93.6%, negative predictive value of 91.0%, and overall accuracy of 92.5%. Subgroup analysis revealed optimal performance in children aged 9-12 years (93.8% accuracy) and normal-weight patients (93.8% accuracy), with reduced accuracy in overweight/obese children (84.2%). Complicated appendicitis showed higher sensitivity (98.1%) compared to simple appendicitis (91.0%). Alternative diagnoses were identified in 13.8% of patients, with mesenteric lymphadenitis being most common. Conclusion: Ultrasound demonstrates excellent diagnostic accuracy for pediatric appendicitis and should be considered the first-line imaging modality. The high diagnostic performance, combined with absence of radiation exposure and cost-effectiveness, supports implementation of standardized ultrasound protocols in pediatric emergency departments for optimal patient care and resource utilization.